The Effect of Brand Identity and Brand Preference on Starbucks Repurchase Interest in Bekasi City - Raehan Pratama Dias; Nurini Ika Kusuma (Jurnal Ekonomi dan Bisnis Digital, 2023)
Starbucks is a premium coffee shop that has been present in Indonesia for 20 years and is part of the lifestyle of urban communities in Indonesia. The aim of this research, firstly, is to determine the influence of brand identity on repurchase intention. Then, to find out the influence of brand preference on repurchase intention. This study uses a component-based SEM (Structural Equation Modeling) using PLS (Partial Least Square) to analyze the data. The results of the study show that Brand Identity and Brand Preference contribute to repurchasing interest in Starbucks products in the city of Bekasi. Therefore, the better the two variables formed by Starbucks for consumers, the better the level of interest in repurchasing Starbucks products in Bekasi City.